Atomic layer deposition for efficient oxygen evolution reaction at Pt/Ir catalyst layers - Schlicht, Stefanie; Percin, Korcan; Kriescher, Stefanie; Hofer, André; Weidlich, Claudia; Wessling, Matthias; Bachmann, Julien (Beilstein Journal of Nanotechnology, 2020)
We provide a direct comparison of two distinct methods of Ti felt surface treatment and Pt/Ir electrocatalyst deposition for the positive electrode of regenerative fuel cells and vanadium–air redox flow batteries. Each method is well documented in the literature, and this paper provides a direct comparison under identical experimental conditions of electrochemical measurements and in identical units. In the first method, based on classical engineering, the bimetallic catalyst is deposited by dip-coating in a precursor solution of the salts followed by their thermal decomposition. In the alternative method, more academic in nature, atomic layer deposition (ALD) is applied to the felts after anodization. ALD allows for a controlled coating with ultralow noble-metal loadings in narrow pores. In acidic electrolyte, the ALD approach yields improved mass activity (557 A·g−1 as compared to 80 A·g−1 at 0.39 V overpotential) on the basis of the noble-metal loading, as well as improved stability.
Keywords: atomic layer deposition (ALD); oxygen evolution reaction (OER); redox flow battery; vanadium–air redox flow battery (VARFB)

(untitled) - Yan, D.; Li, Y.; Huo, J.; Chen, R.; Dai, L.; Wang, S. (Adv. Mater. (Weinheim, Ger.), 2017)

(untitled) - Lee, Y.; Suntivich, J.; May, K. J.; Perry, E. E.; Shao-Horn, Y. (J. Phys. Chem. Lett., 2012)

(untitled) - Jiao, Y.; Zheng, Y.; Jaroniec, M.; Qiao, S. Z. (Chem. Soc. Rev., 2015)

(untitled) - Sadhasivam, T.; Dhanabalan, K.; Roh, S.-H.; Kim, T.-H.; Park, K.-W.; Jung, S.; Kurkuri, M. D.; Jung, H.-Y. (Int. J. Hydrogen Energy, 2017)

(untitled) - Carmo, M.; Fritz, D. L.; Mergel, J.; Stolten, D. (Int. J. Hydrogen Energy, 2013)

(untitled) - Hosseiny, S. S.; Saakes, M.; Wessling, M. (Electrochem. Commun., 2011)

(untitled) - Zhu, Y. G.; Jia, C.; Yang, J.; Pan, F.; Huang, Q.; Wang, Q. (Chem. Commun., 2015)

(untitled) - Jörissen, L. (J. Power Sources, 2006)

(untitled) - Dresp, S.; Luo, F.; Schmack, R.; Kühl, S.; Gliech, M.; Strasser, P. (Energy Environ. Sci., 2016)

(untitled) - Zhang, J.; Zhao, Z.; Xia, Z.; Dai, L. (Nat. Nanotechnol., 2015)

(untitled) - Cheng, Y.; Jiang, S. P. (Prog. Nat. Sci.: Mater. Int., 2015)

(untitled) - Schlicht, S.; Haschke, S.; Mikhailovskii, V.; Manshina, A.; Bachmann, J. (ChemElectroChem, 2018)

(untitled) - Jirkovský, J.; Makarova, M.; Krtil, P. (Electrochem. Commun., 2006)

(untitled) - Tung, C.-W.; Hsu, Y.-Y.; Shen, Y.-P.; Zheng, Y.; Chan, T.-S.; Sheu, H.-S.; Cheng, Y.-C.; Chen, H. M. (Nat. Commun., 2015)

(untitled) - Shin, S.; Choi, Y.-W.; Choi, J. (Mater. Lett., 2013)

(untitled) - Song, S.; Zhang, H.; Ma, X.; Shao, Z.; Baker, R. T.; Yi, B. (Int. J. Hydrogen Energy, 2008)

(untitled) - Honoré Kondro, K.; Ouattara, L.; Trokourey, A.; Bokra, Y. (Bull. Chem. Soc. Ethiop., 2008)

(untitled) - Li, F.-M.; Gao, X.-Q.; Li, S.-N.; Chen, Y.; Lee, J.-M. (NPG Asia Mater., 2015)

(untitled) - Puurunen, R. L. (J. Appl. Phys., 2005)

(untitled) - Bachmann, J. (Beilstein J. Nanotechnol., 2014)

(untitled) - Kriescher, S. M. A.; Kugler, K.; Hosseiny, S. S.; Gendel, Y.; Wessling, M. (Electrochem. Commun., 2015)

(untitled) - Schlicht, S.; Barr, M. K. S.; Wu, M.; Hoppe, P.; Spiecker, E.; Peukert, W.; Bachmann, J. (ChemElectroChem, 2018)

(untitled) - Schlicht, S.; Büttner, P.; Bachmann, J. (ACS Appl. Energy Mater., 2019)

(untitled) - Devilliers, D.; Dinh, M. T.; Mahé, E.; Krulic, D.; Larabi, N.; Fatouros, N. (J. New Mater. Electrochem. Syst., 2006)

(untitled) - Zazpe, R.; Knaut, M.; Sopha, H.; Hromadko, L.; Albert, M.; Prikryl, J.; Gärtnerová, V.; Bartha, J. W.; Macak, J. M. (Langmuir, 2016)

(untitled) - King, J. S.; Wittstock, A.; Biener, J.; Kucheyev, S. O.; Wang, Y. M.; Baumann, T. F.; Giri, S. K.; Hamza, A. V.; Baeumer, M.; Bent, S. F. (Nano Lett., 2008)